Kiddy Brain Games 1 - 2 tahun : permainan untuk menumbuhkan bakat anak anda / Trusty T Santoso ; editor, Amanda Setiorini, Theresia Vini S. - Santoso , Trusty T.; Vini S , Theresia; Setiorini, Amanda (Esensi)
61 hlm ilus 10 cm